Penyusutan Arsip Dinamis Inaktif di Kantor Dewan Perwakilan Rakyat Daerah (DPRD) Provinsi Sumatera Barat - Saputri, Yana; Rahmah, Elva (Ilmu Informasi Perpustakaan dan Kearsipan, 2013)
The purposes of this study were are to explain about step of shrinkage inactive dynamic archives office regional parlements (DPRD) province West Sumatera and describe what are the obstacles faced in doing of shrinkage inactive dynamic archives office DPRD province West Sumatera. Technique of analyzing data is done by describing the interview, describing the results of direct observation, data has been obtained in accordance with the theory discussed, conclusions, and reporting. The results of this study were as are: (1) process shrinkage inactive dynamic archives at office DPRD has not done will, at affice DPRD doingÂ  shrinkage with inventory; (2) the obstacles faced in doing of shrinkage inactive dynamic archives at office DPRD province West Sumatera are lack of expertis, the absence of records retention schedules, lack of infrastructure and the lack of budget funds are doing of shrinkage at office DPRD Province West Sumatera. Keywords: inactive dynamic archives; records retention